HOW SOCIAL MEDIA, EMOTIONAL ATTACHMENT, AND DESTINATION IMAGE DRIVE MUSEUM’S VISIT INTENTION: THE ROLE OF INFLUENCER CREDIBILITY AT MOJA MUSEUM - Miharni Tjokrosaputro; Haris Maupa; Rorlen Rorlen (Jurnal Manajemen dan Kewirausahaan, 2026)
Nowadays, as museums are increasingly promoted as attractive tourist destinations, digital marketing plays an essential role in attracting more visitors, especially through social media and influencer engagement. This research examined how social media marketing (SMM) and influencer credibility shaped visit intention to Moja Museum by assessing the mediating roles of emotional attachment and destination image. A descriptive quantitative approach was applied, and data were collected from 247 purposively selected respondents exposed to Moja Museum’s social media content. The findings showed that influencer credibility significantly enhanced emotional attachment and destination image, but did not directly influence visit intention. Emotional attachment and destination image served as mediators in this pathway. Conversely, SMM directly and significantly affected both destination image and visit intention, although destination image did not mediate the latter. These results contributed to the advancement of Source Credibility Theory in museum tourism by highlighting affective and cognitive mechanisms behind visitor behavior. From a practical perspective, the study suggested that credible influencers fostered emotional bonds and positive perceptions, while well-crafted social media campaigns directly encouraged visit intentions.